2013
DOI: 10.1016/j.jyp.2013.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel and the possibility of drug–drug interaction in primary health care

Abstract: a b s t r a c tIntroduction: Clopidogrel ineffectiveness is a serious problem in antiplatelet therapy. Many factors may contribute to this phenomenon. One of them is clopidogrel drugedrug interaction with CYP2C19 and CYP3A4 enzyme inhibitors. The main goal of this descriptive study was to assess the prevalence of cases of clopidogreledrug interactions in the primary health care physicians' practices. Materials and methods: During 2010e2011, 80 patients receiving clopidogrel antiplatelet therapy from primary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The CCBs and Statins are used widely in cardiology, and the chance of their co-administration with clopidogrel is very high (Urtane et al, 2013). CCBs inhibit CYP3A4, interfere with the activation of clopidogrel (Siller-Matula et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The CCBs and Statins are used widely in cardiology, and the chance of their co-administration with clopidogrel is very high (Urtane et al, 2013). CCBs inhibit CYP3A4, interfere with the activation of clopidogrel (Siller-Matula et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies analyzed the prevalence of PPI and clopidogrel coprescription, demonstrating that there is a wide range of coprescription rates Momary and Cavallari 2010;Bhurke et al 2012;Urtane et al 2013). Juurlink et al (2009) found 20% of coprescriptions for 13,636 patients in Ontario, and Ho et al (2009) found a higher rate of 64% for all patients discharged from any Veteran Affairs hospitals with acute myocardial infarction or unstable angina.…”
Section: Discussionmentioning
confidence: 99%
“…Drug interactions are influenced by many factors. Clopidogrel is metabolized through CYP450, a variety of isozymes are involved in this process, such as CYP1A2, CYP2C9, CYP2D6, and CYP3A5, 32 35 except the 2 most important CYP3A4 and CYP2C19. The combination of CYP3A4 and CYP2C19 inhibitors may be not sufficient to affect the metabolism of clopidogrel.…”
Section: Discussionmentioning
confidence: 99%